Do mundo do texto ao mundo da vida: recepção de narrativas literárias de Clarice Lispector e Lygia Fagundes Telles por mulheres de mais de cinquenta anos participantes do Programa Trabalho Social com Idosos – SESC/Ce - Souza, Nathalia Sobral de (2012)
This work has as proposal a study about the female aging starting from the reception of literary narrative readings of the writers Clarice Lispector and Lygia Fagundes Telles by women of more than fifty years who participate in the Literary Creation Group of the Social Work with the Elderly - TSI program. SESC / CE. Through the encounter between the women of the text world and the women of the world of life, provided by the reading of the stories, we seek to understand the ways in which these women understand their trajectories, now transformed by the aging process, as well as what makes them look Ways of resignifying their experiences and removing from themselves the image of old age as a stage of life associated with stigmas and restrictions linked mainly to bodily limitations, exit from the labor market, changes in family relationships, etc.